Evaluation of the Teacher Performance Program in Improving the Quality of Education at MTsN Binjai - Nasution, Inom; Adela, Risa; Putri, Eliza; Syuhadi, Fikri; Maghfiroh, Lusi; Gembira, Muhammad; Br Situmorang, Heni Sovia (IKAMAS: Manajemen Pendidikan Islam, 2023)
Abstrack:The purpose of this research is theoretically from the results of the discussion of this research are expected to make a scientific contribution, for scientific development, provide input to the school in terms of evaluating teacher performance in improving the quality of education, evaluation materials for Mtsn Binjai to provide better educational evaluations, for researchers expected to be a contribution and add to the literature for educational studies. This research was conducted at MtsN Binjai. West Rambung, South Binjai District. Binjai City, North Sumatra. This research was carried out in March 2023. All educators who teach at MtsN Binjai. Rambung Barat, South Binjai District with a total of 348 male students and 431 female students. Data collection uses observation sheets, questionnaires, interviews and documentation. Based on the data obtained, it can be concluded that: teacher performance evaluation concerns planning and learning, teacher performance in implementing learning, teacher performance in assessing learning outcomes, also teacher discipline in carrying out their duties has good performance. So that the quality of education in these schools is of good value.Keywords: Purpose ; Methods ; Results ; Conclusion.